„Enemy nationalities“ – the Fate of the Lithuanian population of German origin at the end of the Second World War - Burauskaitė, Teresė Birutė (Genocidas ir rezistencija, 2024)
Repressive politics of the Soviet Union is examined rather well by Russian and Lithuanian researchers. Many of the most important archive documents and research works on the repressions against Lithuanian people are published. Few, however, know of the deportation from Lithuania to Tadjikistan persons of German ancestry at the end of Second World War. Only one book of 70 pages in 1992 and some articles in the newspapers have been published about deportation of this national minority of Lithuania. In this article the attempt have made to define the criteria of selection and other circumstances of the deportation of 908 persons of German ancestry on the 22–26 of April, 1945, by using electronic basis of data gathered in the Centre of the Research of Genocide and Resistance in Lithuania (further – EBD ), documents from the previous KGB archive and the manuscript recollections of the deportees themselves. One tenth of Lithuanian people had been repressed on their social or national origin during Soviet occupation 1940–1941 and 1944–1990. The implementation of the Instruction on the deportation of anti-soviet elements from Baltic countries, signed by I. Serov on October 11, 1939, begun on July, 1940. In this document like “enemies of people” had been defined persons, who repatriated from Germany, Germans, who signed to be repatriated, but refused to leave and persons, who had relatives in Germany. Later category “who has relatives in Germany” was excluded, but the category “people, who tried to escape to Germany under the coverage of repatriation” was added. According to those categories, 3670 people were registered. Taking into consideration that in 1940 36 000 Germans and some 500 citizens of Germany lived in Lithuania, every one German of ten was to be deported. According to the data of EBD , in Lithuania before the beginning of German – Soviet War were repressed 106 ethnical Germans, among them: 23 were deported, 4 of them died in exile; 69 arrested, 8 of them were released during the first days of the German – Soviet War, 17 were passed to Germany according to the Agreement of the Exchange, 14 died in the places of confinement; there are no data about 30 prisoners; for 14 people the category of repression is not set. Russian sociologist V. Zemskov have maintained that this group of deportees (in all 12 682 persons from Lithuania were deported in June, 1941) was replaced in the settlements under the most strict regime than kulak deportees because of their “higher social danger”. The beginning of German – Soviet War and the Nazi occupation ruined Soviet plans of liquidation of the “anti-soviet element” in Lithuania. During World War Two USR government viewed Soviet Germans and others of “enemy ancestry” as potentially dangerous diversionists and spies. All the Russian Germans were deported from Volga region to Novosibirsk, Omsk regions, Altai land, Kazakhstan SSR and statehood of Volga German region have been liquidated according the Decree of the Presidium of High Soviet of the USR on August 28, 1941. In 1941–1942 1200 thousand Soviet citizens of German ancestry were deported. Men were to be deported of the age of 15–55 and women – 16–45, together with children not younger than three years old. All of them were mobilized to the so called “labour armies”, where they in the half-starved circumstances were forced to work in the very hard climate conditions and to live in the unsuitable for living premises without heating. In summer 1944 Red Army pushed out German occupants from the Lithuanian territory. After them came the soldiers of NKVD, prepared to go on with repressions against Lithuanian people. The first deportations after the war fell on the ethnical Germans in Lithuania, as they were considered “the enemy nationality”. In Special Archive of Lithuania decrees are preserved about the deportation of 626 people (200 families). In these documents the persons, selected for deportation, were incriminated for the aiding of German occupants, for their German ancestry itself or the relative relations with persons of German nationality. 94 of them were of Lithuanian nationality and they were only members of the families of ethnical Germans. According to the data of EBD , on April 22–26, 1945, 906 ethnical Germans and members of their families were deported from Lithuania. All of them were gathered in Kaunas on April 22–26 from the Southern and Western parts of Lithuania, and because of the lack of wagons have been sent into exile only on the third of May. Their route is mysterious even today: on the first days of May the echelon moved to the North up till Vologda, on the 9th of May deportees were allowed to wash themselves in the bathroom in favor of Victory, and then the train turned to the South. At the beginning of June deportees were brought to the cotton plantations in the valley of the river Vakhsh, Kuibyshevsk region, Tadjik SSR . There were inhuman living conditions: starvation, lack of drinking water, unsanitary conditions in the living apartments, servitude in heat led to the premature deaths. 341 (37,5%) deportees of the total number 908 died there, 255 of them in the period 1945–1947, e.g. 75%. In the other countries, which were on war against Germany and its allies, USA, Britain and Canada, citizens of “enemy nationality”: Germans, Japanese and Italians were also isolated in different ways. Pursuant to President of the USA Franklin Roosevelt Executive Order 9066, signed on February 19, 1942, the military power could restrict the liberties of citizens and aliens, as it deemed necessary. This led to the exclusion and internment of individuals and groups of “the enemy nation”. During World War Two, the US Government interned at least 11,000 persons of German ancestry and 120 thousand Japanese. By law, only “enemy aliens” could be interned. However, with governmental approval, their family members frequently joined them in the camps. Many such “voluntarily” interned spouses and children were American citizens. Internment was frequently based upon uncorroborated, hearsay evidence gathered by the FBI and other intelligence agencies. Homes were raided and many ransacked. Potential internees were held in custody for weeks in temporary detention centers, such as jails and hospitals, prior to their hearings without the evidence of attorneys. Sometimes children left after the arrests had to fend for themselves. Some were placed in orphanages. Eventually, under such duress, hundreds of internees agreed repatriate to war-torn Germany to be exchanged with their children for Americans. Once there, food was scarce, Allied bombs were falling and their German families could do little to help them. Many regretted their decision. Internees live in the camps of common regime under armed guard and strictly regulated contacts with the outer world. The internees lost part of their properties, the salary was made lower, in camps there were not enough schools for children and they lived under the armed guard. But neither in the recollections of internees, nor in the research works on the violation of human rights, there are any data about the influence of living conditions in the camps on the diseases and deaths of the interned.. While summarizing we can say that the living conditions of the deported Soviet citizens of German ancestry could not meet the elementary demands of surviving. We can judge that the deportation of Soviet citizens of the “enemy nationality” had the aim not only to grant security of the country at war time. According to the opinion of the widely known Russian sociologist V. Zemskov, the conditions of war time were used by Stalin “to speed the assimilation processes in Soviet society”.